Use of Clinical Audits to Evaluate Timing of Preoperative Antimicrobials in Equine Surgery at a Veterinary Teaching Hospital - Ceriotti, Serena; Westerfeld, Roxane; Bonilla, Alvaro G.; Pang, Daniel S. J. (Frontiers in Veterinary Science, 2021)
Based on human surgical guidelines, intravenous antimicrobials are recommended to be administered within 60 min of surgical incision. Achieving this target in horses is reportedly challenging and influenced by hospital policies. The objectives of this study were to evaluate and improve: (1) the timing of antimicrobial administration to surgical incision (tAB-INC), (2) contributions of anesthesia pre-induction (tPRI) and surgical preparation (tPREP) periods to tAB-INC, and the (3) completeness of antimicrobial recording. Two clinical audits were conducted before and after the policy changes (patient preparation and anesthesia record keeping). tPRI, tPREP, and tAB-INC were calculated and compared for elective arthroscopies and emergency laparotomies within and between the audits. The percentage of procedures with a tAB-INC <60 min was calculated. Antimicrobial recording was classified as complete or incomplete. A median tAB-INC <60 min was achieved in laparotomies (audit 1; 45 min, audit 2; 53 min) with a shorter tPREP than arthroscopies (p < 0.0001, both audits). The percentage of procedures with tAB-INC <60 min, tAB-INC, tPRI, and tPREP durations did not improve between the audits. There was a positive correlation between the number of operated joints and tPREP (audit 1, p <0.001, r = 0.77; audit 2, p < 0.001, r = 0.59). Between audits, antimicrobial recording significantly improved for elective arthroscopies (82–97%, p = 0.008) but not emergency laparotomies (76–88%, p = 0.2). Clinical audits successfully quantified the impact of introduced changes and their adherence to antimicrobial prophylaxis guidelines. Antimicrobial recording was improved but further policy changes are required to achieve a tAB-INC <60 min for arthroscopies.